Nonmetrical variants of the sigmoid sulcus: A study on dry human skulls - Rakesh Kumar Diwan; Rakesh Kumar Verma; Arvind Kumar Pankaj; Anita Rani; Navneet Kumar (Wolters Kluwer Medknow Publications, 2021)
Background: Sigmoid sinus is an area of interest for anatomists, neurosurgeons, and radiologists. Different procedures such as mastoidectomy, thrombectomy in the sigmoid, and transverse sinus thrombosis have realized the need of proper morphological knowledge of the sigmoid sinus and its variations and their important relations. Therefore, the present study was conducted to report the prevalence of various nonmetrical attributes of the sigmoid sulcus in dry human skulls in India. Methodology: This study was conducted on 224 human skulls in which sex and origin were not known and these were taken from the departmental osteology laboratory. Interior of the skull base at the area of the sigmoid sulcus was carefully observed for the presence of any osseous projection on its anterior or posterior lips such as crest, plate, or bars. Shape, position, and side of projection were noted and frequency was calculated in percentage. Results: Out of 224 skulls, 80% of the sigmoid sulci showed one or other form of bony features. A total prevalence of 43.08% was observed for crests, whereas plates showed lesser frequency (28.57%) on the anterior lip of the sigmoid sulcus. Bony bars were the least common (9.14%) features, but were characteristically located at the angle region of the sigmoid sulcus. In 16.74% of skulls, sigmoid sulcus was shallow. Conclusion: Occurrence of bony attributes in the form of plates, crests, and bridges along the course of the sigmoid sulcus is quite high and shows frequent variability in location and laterality, which may adversely affect the morphology of the sigmoid sinus.